Evaluasi Program Pembangunan Ekonomi Nasional yang Mengacu pada Nilai Pancasila: Evaluation of the National Economic Development Program Referring to Pancasila Values - Atikah Nur Rahmah; Meydina Yohanita Putri; Azizah Dzakiatul Ulya; Maulida Fatimatuz Zahro (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
National economic development is a key pillar in realizing the welfare of the Indonesian people. However, in its implementation, economic development often ignores the fundamental values embodied in Pancasila. This study aims to evaluate the effectiveness of national economic development programs by reviewing their alignment with Pancasila values, particularly in terms of social justice, unity, and humanity. The method used was a qualitative approach with document studies and in-depth interviews with stakeholders at the central and regional levels. The evaluation results indicate that some development programs align with Pancasila values, particularly in efforts to empower the people's economy and reduce inequality. However, a number of programs were also found to not reflect the principles of justice and equal participation. The conclusion of this study emphasizes the importance of explicitly integrating Pancasila values into the planning, implementation, and evaluation of national economic policies to ensure inclusive and sustainable development.